3j-(j-4)+3=

Simple and best practice solution for 3j-(j-4)+3= equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for 3j-(j-4)+3= equation:


Simplifying
3j + -1(j + -4) + 3 = 0

Reorder the terms:
3j + -1(-4 + j) + 3 = 0
3j + (-4 * -1 + j * -1) + 3 = 0
3j + (4 + -1j) + 3 = 0

Reorder the terms:
4 + 3 + 3j + -1j = 0

Combine like terms: 4 + 3 = 7
7 + 3j + -1j = 0

Combine like terms: 3j + -1j = 2j
7 + 2j = 0

Solving
7 + 2j = 0

Solving for variable 'j'.

Move all terms containing j to the left, all other terms to the right.

Add '-7' to each side of the equation.
7 + -7 + 2j = 0 + -7

Combine like terms: 7 + -7 = 0
0 + 2j = 0 + -7
2j = 0 + -7

Combine like terms: 0 + -7 = -7
2j = -7

Divide each side by '2'.
j = -3.5

Simplifying
j = -3.5

See similar equations:

| y=arcsin(x+2) | | -12x=-70 | | 4x-7=3.8 | | 5x+4x=70 | | 6(x-3)-4x=32 | | 4(-3.4)+1/3=(-3.4)-5/2 | | 0.03x-0.4x=2.85 | | a+0.8=-0.8a+3.86 | | 28+4x=156 | | -10=8x-3 | | 4(x+2)-6x+4=-42 | | 2+x=58 | | (-a^2+2)-(a^2-4)+(6a^2-5a*3)= | | 5x+140= | | .7=.35 | | 4s-12=5s+15 | | (4x^2+9x-2)+(4x^2+4x+19)-(8x^2-14)= | | 3(2x-1)=3x+1/2 | | 8K+1-1=17 | | 3(12-x)+6x=10 | | x+4=5x-20 | | 96=3(4x-8) | | 5(m-4)+6m=5(m+3)-7 | | -10x^2+6x+3=0 | | 2(3x+4)+2x=11x-4+x | | Y=12x^2+24 | | 8x+1=6(1+3x)-2(5x-6) | | 3(2x-7+5x)=x-1 | | F(x)=12x^2+24 | | H=-16t^2+128t+5 | | -6a-36=-4(3a+3) | | 3x+129= |

Equations solver categories